Great mistakes in education policy : and how to avoid them in the future - Lupton, Ruth; Hayes, Debra, 1960- (Book collections on Project MUSE., 2021)
Situating the cases of England and Australia within broader global policy trends, this book critically analyses what has gone wrong with education policy. Drawing on wide-ranging research, the authors issue a fundamental challenge to current policy orthodoxies, and identify policy alternatives to make education both better and fairer.